Sitti Raihanun: Female cleric and initiator of prominent Islamic educational institutions in Lombok, West Nusa Tenggara - Nasri, Ulyan; Atsani, Lalu Gede Muhammad Zainuddin (Univeritas Papua, 2024)
Sitti Raihanun, as a female cleric in Lombok, West Nusa Tenggara, plays a pivotal role in the establishment of prominent Islamic educational institutions in the 21st century. This study aims to explore the role and contributions of Sitti Raihanun in the development of Islamic educational institutions in the region. Historical research methodology is employed in this study, involving the collection and analysis of primary sources. Data collection technique: data is obtained through interviews with Sitti Raihanun, stakeholders, and the collection of relevant documents. The data analysis technique is conducted using a qualitative approach to depict the role, strategies, and impact of Sitti Raihanun's activities in Islamic education. The results of this study indicate that Sitti Raihanun successfully formed quality Islamic educational institutions, increased community participation, and had a positive impact on religious understanding. The implications of this research lie in empowering the community through quality Islamic education, with the potential for widespread positive impact at the local, national, and even international levels.